An Ordinance Respecting Public Balls, New Orleans, LA (Passed 27 Oct. 1817) - (:unkn) unknown (My University, 1817)
Prohibited any person from entering any public ballroom with any cane, stick, sword, or any other weapon. Such weapons shall be checked in at the entrance with receipt documentation.
Keywords: SENSITIVE PLACES